1991
DOI: 10.1029/90jd00290
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparing shortwave radiation codes for climate studies

Abstract: As a second step of the international program of Intercomparison of Radiation Codes Used inClimate Models (ICRCCM), an intercomparison of shortwave radiation models was initiated. Among the 26 codes that participated in the comparison were very detailed (line-by-line), narrow-band (high-spectral resolution), as well as highly parameterized (low-spectral resolution) models. A considerable spread was detected in the response of these models to a set of well-defined atmospheric profiles. Substantial discrepancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 30 publications
5
82
0
3
Order By: Relevance
“…The surface and TOA fluxes are likewise improved from the >10% errors that were seen to occur in RF92. Results are presented for three cloud locations: 180-900, 300-900, and 500-900 mbar using the CS drop model from the ICRCCM specifications [Fouquart et al, 1991] …”
Section: Total Spectrummentioning
confidence: 99%
“…The surface and TOA fluxes are likewise improved from the >10% errors that were seen to occur in RF92. Results are presented for three cloud locations: 180-900, 300-900, and 500-900 mbar using the CS drop model from the ICRCCM specifications [Fouquart et al, 1991] …”
Section: Total Spectrummentioning
confidence: 99%
“…Fouquart et al (1991) examined 26 radiation schemes ranging from high to low spectral resolution and found substantial discrepancies in computed fluxes for even the simplest prescription of only pure water vapor absorption. When including highly scattering aerosols and a fixed surface albedo, the relative standard deviation for the eleven models considered ranged from 23 to 114 % as the solar zenith angle (SZA) decreased from 75 • to 30 • (Fouquart et al, 1991;Boucher et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fouquart et al (1991) examined 26 radiation schemes ranging from high to low spectral resolution and found substantial discrepancies in computed fluxes for even the simplest prescription of only pure water vapor absorption. When including highly scattering aerosols and a fixed surface albedo, the relative standard deviation for the eleven models considered ranged from 23 to 114 % as the solar zenith angle (SZA) decreased from 75 • to 30 • (Fouquart et al, 1991;Boucher et al, 1998). Boucher et al (1998) found that the relatively high (8 %) standard deviation in zenith angle-average broadband forcing due to prescribed non-absorbing sulfate aerosols was due to differences in the treatment of Mie scattering, multiple scattering, phase functions, and spectral and angular model resolution.…”
Section: Introductionmentioning
confidence: 99%
“…These models have been derived from a detailed radiative-convective model (Vardavas and Carver, 1984) and have been successfully tested (see Vardavas and Koutoulaki, 1995;Hatzianastassiou et al, 1999) according to the Intercomparison of Radiation Codes in Climate Models (ICRCCM) program (Fouquart et al, 1991). The same models have already been used to predict the long-term mean monthly 10°zonal radiation budgets for both SW and LW radiation (Vardavas and Koutoulaki, 1995;Vardavas, 1999a,b, 2001a,b;Hatzianastassiou et al, 1999Hatzianastassiou et al, , 2001, and also to derive the downwelling LW flux at the surface on a 2.5°resolution for the entire globe (Pavlakis et al, 2004).…”
Section: Model and Input Datamentioning
confidence: 99%